Potential role of permafrost thaw on increasing Siberian river discharge - Ping Wang; Qiwei Huang; Sergey P Pozdniakov; Shiqi Liu; Ning Ma; Tianye Wang; Yongqiang Zhang; Jingjie Yu; Jiaxin Xie; Guobin Fu; Natalia L Frolova; Changming Liu (Environmental Research Letters, 2021)
Despite the increasing Siberian river discharge, the sensitivity of streamflow to climate forcing/permafrost thawing is poorly quantified. Based on the Budyko framework and superposition principles, we detected and attributed the changes in streamflow regimes for the three great Siberian rivers (Ob, Yenisei, and Lena) during 1936–2019. Over the past 84 years, streamflow of Ob, Yenisei and Lena has increased by ∼7.7%, 7.4% and 22.0%, respectively. Intensified precipitation induced by a warming climate is a major contributor to increased annual streamflow. However, winter streamflow appears to be particularly sensitive to temperature. Whilst rising temperature can reduce streamflow via evapotranspiration, it can enhance groundwater discharge to rivers due to permafrost thawing. Currently, every 1 °C rise in temperature likely leads to 6.1%–10.5% increase in groundwater discharge, depending on the permafrost condition. For permafrost-developed basins, the contribution to increased streamflow from thawing permafrost will continue to increase in the context of global warming.